Development Possibilities of Tourism in Pello - Leppänen, Anna-Riikka; Korpi, Elina (Rovaniemen ammattikorkeakoulu, 2012)
The purpose of the thesis was to examine the current situation and development needs of tourism industry in Pello in order to provide development tools and knowledge for the local Destination Management Organisation (DMO). Additionally it sets also relevant example for other small communities in Lapland how to benefit from tourism industry as a livelihood. Business to Business co-operation (B2B) and public-private partnerships (PPP) are generally recognized to increase the competitive advantage in destination management. In Fell Lapland as in many other tourism destinations those are the key issues modifying the daily operations of small and medium size enterprises.The research question was how to increase the competitive advantage of Pello as a tourism destination by creating co-operation and public-private partnership? In this analytical thesis process the research methods used included content analysis in making an analysis of the destinations’ operating environment, semi-structured theme interviews in gathering information from the enterprises and benchmarking in comparing the two destinations and learning from best practice. The research proved a lack of resources in developing tourism in Pello. As financial resources and proper marketing are often key issues, there is also lack of co-operation among companies and between the public and private sector. Destination management is not holistic and in order to increase the competitiveness in the destination, a much deeper understanding of the destination needs to be accomplished before directing planning and finances to marketing the destination. However, the attitudes and grounds for development are open and development suggestions for the future were firmly justified. Opinnäytetyön tarkoitus oli tutkia Pellon kunnan matkailun elinkeinon nykytilaa ja kehitysmahdollisuuksia, sekä ehdottaa sopivia kehityksen työkaluja ja tietoa Pellon matkailunkehitysorganisaatiolle. Tämän lisäksi opinnäytetyömme tarjoaa hyvän esimerkin muille samankaltaisille pienille ...